2006
DOI: 10.1111/j.1471-0528.2006.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

How to repair an anal sphincter injury after vaginal delivery: results of a randomised controlled trial

Abstract: Objective To compare two surgical techniques and two types of suture material for anal sphincter repair after childbirth-related injury.Design Factorial randomised controlled trial.Setting Tertiary referral maternity unit.Population Women with an anal sphincter injury sustained during childbirth.Method Women were randomised into four groups: overlap repair with polyglactin (Vicryl); end-to-end repair with polyglactin (Vicryl); overlap repair with polydioxanone (PDS); and end-to-end repair with PDS. All repairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 29 publications
3
48
2
4
Order By: Relevance
“…The experience of physicians performing primary repairs varies, and some may feel inadequately trained to perform an optimal repair. 12,28,29 In cases when the responsible physician feels uncomfortable performing the procedure, our study suggests that delaying the operation until the adequate expertise is in place or up to 12 hours is safe and does not adversely affect anal continence status 1 year after delivery. However, our results do not suggest a benefit in delaying primary repair per se.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The experience of physicians performing primary repairs varies, and some may feel inadequately trained to perform an optimal repair. 12,28,29 In cases when the responsible physician feels uncomfortable performing the procedure, our study suggests that delaying the operation until the adequate expertise is in place or up to 12 hours is safe and does not adversely affect anal continence status 1 year after delivery. However, our results do not suggest a benefit in delaying primary repair per se.…”
Section: Discussionmentioning
confidence: 98%
“…10 A partial sphincter tear is, however, not compatible with an overlap repair, and several trials have concluded equivalence between the methods. 9,11,12 Child deliveries are evenly distributed over the hours and it is plausible that awaiting surgical expertise following detection of an obstetric anal sphincter injury may optimise the subjective outcome. However, it is also possible that the consequential time delay between the injury and the repair will affect the outcome of the repair.…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration is improvement in OASIS recognition and repair. Structured training, use of recommended suture materials and repair techniques are associated with good clinical outcomes [36,43,44]. Attention to the above was driven by the RCOG Green-top guideline first published in 2001 [3].…”
Section: Discussionmentioning
confidence: 99%
“…If not recognised and repaired, this type of tear may lead to a rectovaginal fistula. 25 An increasing incidence of third-or fourth-degree perineal tears does not necessarily indicate poor quality care. But it may rather indicate an improved quality of care through better detection and reporting.…”
mentioning
confidence: 99%
“…Regional or general anaesthesia will facilitate identification of the full extent of the injury and enable retrieval of the retracted ends of the torn anal sphincter. 25 A randomized trial by Williams et al, compared OASIS repairs with polyglactin (Vicryl) and polydioxanone (PDS). They found no significant difference in suturerelated morbidity at 6 weeks.…”
mentioning
confidence: 99%